Cancer treatment and drug-induced QT interval prolongation: A review - Olga D. Ostroumova; Aleksey I. Kochetkov; Valeria A. De (ZAO "Consilium Medicum", 2022)
Anticancer drugs can cause drug-induced prolongation of the QT interval. Prolongation of the QT interval is a known risk factor and an independent predictor of the development of life-threatening ventricular arrhythmias (polymorphic ventricular tachycardia, also called Torsades de Pointes), and sudden cardiac death in patients with and without structural heart disease. Healthcare practitioners should constantly evaluate the benefit/risk ratio prior to initiating treatment as well as continuing the chosen one. Some patients need particular attention, especially those who have risk factors such as comorbidities, taking drugs associated with QT interval prolongation, dehydration and electrolyte imbalance, etc. Despite apparent increase in the awareness among the patients and medical professionals, many scientists suggest that there is a lack of awareness about the true prevalence of these adverse events, which are at least 10 times greater than reported cases. This article discusses anticancer drugs that have an association with QT interval prolongation, and also possible strategies in the treatment of the patients with drug-induced QT interval prolongation.